The Effect of Reminiscence Therapy on Increasing Cognitive Function in the Elderly - Akhmad Yanuar Fahmi; Sholihin Sholihin; Rima Ambarwati; Essy Sonontiko Sayekti (Universitas Ahmad Dahlan, 2021)
Reminiscence therapy is proven to be effective in reducing cognitive disorders among the elderly. However, there are some differences in the method of giving reminiscence therapy, so that further research is needed to determine these differences. This study aimed to determine differences in the effectiveness of mindfulness reminiscence in reducing cognitive disorders in the elderly. This study used a pre-post test quasi-experimental design with a control group. The sample consisted of the elderly at Tresna Werdha Orphanage Glenmore (n = 60) who were divided into 2 groups, namely the intervention group (n = 30) and the control group (n = 30). Data collection of cognitive disorders was taken from the component of cognitive disorders questions on the MMSE questionnaire. Data analysis used paired and unpaired t-test. The results showed that reminiscence therapy was effective in reducing cognitive disorders in the elderly.